Trends of Referrals Throughout the Kingdom, A Retrospective Analysis of the Saudi Medical Appointments and Referrals Centre Registry, Saudi Arabia - Alnassar, Abdulaziz; Aljerian, Nawfal; Alhosaini, Abdulaziz; Alsultan, Ali; Ashry, Lyla; Alharthi, Sawsan; Arafat, Mohammed; Aldhabib, Abdulrahman; Almohaimeed, Ibrahim; Aloqayli, Ahmed; Albanyan, Sara; Alrabiah, Bader; et al. (International Journal of Innovative Research in Medical Science, 2022)
Background: The referral process has a central role within health care systems, acting as a gateway to those requiring certain methods of care and services. The main objective of our study was to assess the trends of referrals across the regions of Saudi Arabia during a four-year period from 2018 to 2021 involving a total of more than 1·6 million referrals. Methods: We conducted a retrospective observational study design of referral data submitted by practitioners from different facilities across all regions within Saudi Arabia. Data was obtained from the Saudi Medical Appointments and Referrals Centre (SMARC) over a four-year timeline from 2018 to 2021, with data including the type of referral, reason for referral, and the required specialty. Results: A total of 1,607,009 referrals across the Kingdom of Saudi Arabia were analyzed. The overall number of referrals have increased dramatically throughout the years with an increase of 55% from the year 2018 to 2021, with most referrals being routine (938,467) (58·3%) composed of inpatient and outpatient types of referrals (Figure 1A). Unavailability of required specialty by the primary provider was the most popular reason for referral (897,461) (55·8%), with General Surgery contributing to the majority of referrals (430,664) (26·7%) (Figures 2A, 3A). Referrals initiated from 2019 to 2021 had an acceptance rate of 55·3% with the remaining being either closed (43·3%) or rejected (0·5%). The nationality of the individual requiring a referral was most likely Saudi, contributing to a total of (1,109,254) (84.8%) referrals from 2019 to 2021 (Tables 4A-4B). Conclusions: Upon assessing trends of referrals across regions of Saudi Arabia, we observed a major increase in referrals starting from the year 2018 to 2021, potentially inflicting harm on the sustainability of high-quality health systems. Further actions should be taken to assess the appropriateness of referrals made, which could aid in identifying areas of inefficiencies and possible rate reduction.